Analysis of the opportunities for using energy from renewable sources in Bulgaria. Issue 1 (1st January 2023) - Zlateva, P; Mileva, N
Abstract: The article considers and analyses the opportunities for introducing installations for using energy from renewable sources (RS) in Bulgaria. The aim is, through an analysis of the newly built installations, to point out the benefits from the production of energy from RS, obtained by fulfilling the objectives of the requirements of the European Union (EU) directives for the EU member states and the national strategy for energy independence of Bulgaria. It has been ascertained that in 2020, according to the European Directive 2009/28/EU, Bulgaria had to achieve a 16% share of energy from renewable sources in the gross final consumption, which it exceeded by 7.32%, achieving 23.32%. It has also been ascertained that the share of renewable energy in the structure of primary energy in Bulgaria is 23.8%. In 2020, Bulgaria has a share of energy from renewable sources in the gross final energy consumption of 23.32%, which exceeds the mandatory national target by 7.32%. In 2020, Bulgaria achieved an installed capacity of 5 224.7 MW and the gross production of electric energy increased to 4 627.4 GWh, which was more than twice compared to 2009. For the achievement of these capacities, the newly built local installations also contributed in the production of energy from RS for the period 2017-2021 by planning regions in Bulgaria.